2008
DOI: 10.1007/s00167-008-0576-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of watching live arthroscopic views on postoperative anxiety of patients

Abstract: Surgery is a stressful experience. Many minor interventions have been shown to cause considerable anxiety in patients, but whether arthroscopy leads to such anxiety is not well-known. Methods for lowering perioperative anxiety have been sought and listening to music or watching a movie have been recommended. The method of permitting patients to watch their own endoscopy has been studied infrequently. Our aim in this study was to find out the effect of watching simultaneous arthroscopic views on postoperative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…[22] Different methods have been used to reduce patient's anxiety such as giving sedatives or advising patients to listen to music of their preferences either preoperatively or during the operation. However, our study devised the method of showing video clipping/images[2324] of various patients going to surgery from PAC room to operation table showing the particular clipping of a specific operation to the patient undergoing some procedure, using questionnaire method devised by the HAM-A scale. By showing video clippings/images, our aim was to tell patient what anesthetic procedure he/she will have to go through, its effects and side effects so that patient should have an idea what is going to happen to him/her at least without increasing his/her anxiety and dispelling misconceptions associated with it.…”
Section: Resultsmentioning
confidence: 99%
“…[22] Different methods have been used to reduce patient's anxiety such as giving sedatives or advising patients to listen to music of their preferences either preoperatively or during the operation. However, our study devised the method of showing video clipping/images[2324] of various patients going to surgery from PAC room to operation table showing the particular clipping of a specific operation to the patient undergoing some procedure, using questionnaire method devised by the HAM-A scale. By showing video clippings/images, our aim was to tell patient what anesthetic procedure he/she will have to go through, its effects and side effects so that patient should have an idea what is going to happen to him/her at least without increasing his/her anxiety and dispelling misconceptions associated with it.…”
Section: Resultsmentioning
confidence: 99%
“…Luck et al [15] recommended giving video supported information to patients before the procedure. Bayar et al [6] had their patients watch the surgery from a monitor and reported good results. Bayar et al [6] also reported that reducing the anxiety of patients increased the postoperative satisfaction of the patient about the sense of being cured.…”
Section: Discussionmentioning
confidence: 99%
“…Bayar et al [6] had their patients watch the surgery from a monitor and reported good results. Bayar et al [6] also reported that reducing the anxiety of patients increased the postoperative satisfaction of the patient about the sense of being cured. However, Kesari et al [7] reported that watching their own cystoscopy made no significant difference in patients' anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations